If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying -25 = x + -18 Reorder the terms: -25 = -18 + x Solving -25 = -18 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -25 + -1x = -18 + x + -1x Combine like terms: x + -1x = 0 -25 + -1x = -18 + 0 -25 + -1x = -18 Add '25' to each side of the equation. -25 + 25 + -1x = -18 + 25 Combine like terms: -25 + 25 = 0 0 + -1x = -18 + 25 -1x = -18 + 25 Combine like terms: -18 + 25 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7

| 105=s-7.3 | | -49+m=13 | | 9x-20=5x | | 6x-48=30 | | 4y-7+4y-9= | | 2y-6+3y-7= | | -3+15=13y-5-12x | | 10-x=4 | | 10x=80 | | 16x+5=7x+2 | | 5x-10=3x+5 | | 2x-5=3x+5 | | x-7=2x+3 | | 10x+10=-20+20 | | 35x-10=4x+20 | | 10x+20=30x+10 | | 2x+5=3x+5 | | -10x+10=-20+20 | | 3t+1=7-t | | 12x+2=38 | | 19m-3m=13 | | 19-3m=13 | | 26-5t=3t+2 | | 6(a-3)=2(a+5) | | 13x+11=-16 | | 9x-1=4x+10 | | 3x-7=5x+13 | | 3x+7=5x-13 | | 5x+6=21 | | 4x-6=-50 | | -3+x+x=-11 | | 2+7x-3x=6 | | 5+4x+7x=-17 | | 7x+9-6x=1 | | 8-4x-2x=-52 | | 4-2z=12 | | 5x-10x+12=-3x+6 | | 10x+17x-9+1=8x+1-9 | | 7(5x+9)+(x+9)=12 | | 9(3x+6)+(x+2)=14 | | 2x+6(x-4)=2(x-6) | | -9m+12-5(m-1)=2m-(7m-7)-5m+2 | | D=jr | | P=a+4b+2c | | 6x+4+3x=85 | | 4x-1-x=35 | | -2x+10+6x=22 | | -7+6x+5x=125 | | 4+7x+6x=-22 | | x+8+6x=36 | | -27=2x+3x+3 | | 6x+1+2x=9 | | -6x+6-4x=-14 | | -2-4x=-6x-14 | | 12x+8-3=11x-3 | | 4x+7=42-x | | 3x-1=11-2x | | 4.4q-4.5-3.9q=-0.5q-5.1 | | -9(2b+4)+(19b-5)=0 | | -3x+6=-42+5x | | 3-7x=-4x+3 | | 2x+5=-17+4x | | 6z+8z=126 | | 4x-4=x+29 | | 6x+1=5x+9 |